Osip Mandelstam and the Modernist Creation of Tradition. - Cavanagh, Clare (JSTOR EBA., 2001)
If modernism marked, as some critics claim, an "apocalypse of cultural community," then Osip Mandelstam (1891-1938) must rank among its most representative figures. Born to Central European Jews in Warsaw on the cusp of the modern age, he could claim neither Russian nor European traditions as his birthright. Describing the poetic movement he helped to found, Acmeism, as a "yearning for world culture," he defined the impulse that charges his own poetry and prose. Clare Cavanagh has written a sustained study placing Mandelstam's "remembrance and invention" of a usable poetic past in the context.